Hubungan antara Father Involvement dengan Brain Rot pada Remaja Akhir - Sulle Silambi, Metanika; Putrikita, Katrim Alifa; Fatimah, Malida (UPT Perpustakaan UIN Alauddin Makassar, 2025)
The phenomenon of brain rot, characterized by a decline in cognitive function due to excessive consumption of shallow digital content such as short videos, is increasingly found among late adolescents. This period represents a critical stage of development marked by growing independence and intensive media exploration. Paternal involvement in parenting is presumed to have a protective role in adolescents' digital behavior, but its relevance to brain rot remains underexplored. This study aims to examine the relationship between father involvement and the level of brain rot in late adolescents. A correlational quantitative method was employed. The participants consisted of 151 late adolescents (aged 18–21) selected through purposive sampling. The instruments used were two scales: a father involvement scale and a brain rot scale developed based on eight cognitive functional aspects. Data analysis was conducted using Karl Pearson correlation due to the non-normal distribution of the data. The results showed no significant relationship between father involvement and brain rot (r = -0,010; p = 0,908). These findings indicate that father involvement does not have a direct contribution to the level of brain rot in late adolescents.